Torrefaction and combustion behaviour of beech wood pellets - Yilgin, Melek; Duranay, Neslihan; Pehlivan, Dursun (Springer, 2019)
Use of renewable sources is still a crucial option for energy supply in view of environmental consequences of fossil fuel-dependent industry. Today, only 10% of world's energy needs have been met by biomass sources. This is lower than expectations considering vast interest on biomass energy and necessitates more practical approaches to substitute fossil fuel usage. Torrefaction is a promising technique to obtain coal-like solids which can be incorporated into today's power systems. In this study, torrefaction of beech wood sawdust pellets and their combustion behaviour were investigated using a vertical furnace with a wire mesh basket and necessary equipments. Torrefaction experiments were made as a poly-particles bed in the basket under nitrogen flow and at 493, 533 and 573 K temperatures corresponding to light, mild and severe conditions, respectively. Combustion experiments, however, were carried out by recording mass of single raw or torrefied burning pellet under natural convection airflow at 873, 973 and 1073 K temperatures. It was observed that mild torrefaction was appropriate to obtain a torrefied product retaining over 75% mass of raw pellets but having calorific values higher than most lignite. Volatiles ignition times of torrefied pellets were affected by their moisture contents. This effect lessened with increasing temperatures due to faster heating of pellets. Although torrefied pellets became more porous as severity of torrefaction increased, their carbon combustion rates were generally lower than those of raw pellets and decreased with combustion temperature as well as torrefaction severity.
Keywords: Beech wood; Pellet; Torrefaction; Combustion